2020
DOI: 10.3168/jds.2020-18461
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association analysis for body, udder, and leg conformation traits recorded in Murciano-Granadina goats

Abstract: Morphological traits are of great importance to dairy goat production given their effect on phenotypes of economic interest. However, their underlying genomic architecture has not yet been extensively characterized. Herein, we aimed to identify genomic regions associated with body, udder, and leg conformation traits recorded in 825 Murciano-Granadina goats. We genotyped this resource population using the GoatSNP50 BeadChip (Illumina Inc., San Diego, CA) and performed genomewide association analyses using the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…However, since 2014, low-cost gene chips have had a broad impact on the analysis of the genetic structure of traits of economic interest, as well as on the study of goat population structures at a global scale [ 32 , 33 ]. Luigi-Sierra et al [ 8 ] used the GoatSNP50 BeadChip (Illumina Inc., San Diego, USA) to genotype 825 Murciano-Granadina goats and performed a GWAS. They found that two significant SNPs were associated with the medial suspensory ligament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since 2014, low-cost gene chips have had a broad impact on the analysis of the genetic structure of traits of economic interest, as well as on the study of goat population structures at a global scale [ 32 , 33 ]. Luigi-Sierra et al [ 8 ] used the GoatSNP50 BeadChip (Illumina Inc., San Diego, USA) to genotype 825 Murciano-Granadina goats and performed a GWAS. They found that two significant SNPs were associated with the medial suspensory ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bioinformatics approaches have been applied to study the genetic basis of body conformation traits. The PRDM6 gene influences growth-related traits, such as CC, CD, and CW, in the early growth and development of goats [ 8 ]. PITX2 is significantly associated with body height and body length in Guanzhong dairy goats and Hainan black goats [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the litter size has particularly aroused the interest of husbandry enterprises and breeders, as even a slight increase in the litter sizes in goats can considerably profit the breeders. Meanwhile, including morphological traits in the selection criteria is mainly based on their relationships with the other economic traits of goats and sheep [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In dairy goats, the paired-like homeodomain 2 ( PITX2 ) gene was linked to the body height and body length of Guanzhong and Hainan black goats [ 19 ]. In the same trend, the PR/SET Domain 6 ( PRDM6 ) gene was associated with several body conformation traits such as cannon circumference, chest depth and chest width in Murciano-Granadina goats [ 20 ]. In dual-purpose goats, the prolactin receptor ( PRLR ) gene was found to be associated with body length, body height, chest depth, heart girth and cannon circumference in Shaanbei white cashmere goats [ 21 ].…”
Section: Introductionmentioning
confidence: 99%